2019
DOI: 10.1128/aac.02031-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pharmacodynamic Study of Cefiderocol, a Novel Parenteral Siderophore Cephalosporin, in Murine Thigh and Lung Infection Models

Abstract: The pharmacokinetic (PK) and pharmacodynamic (PD) parameters which correlated with the in vivo efficacy of cefiderocol were evaluated using neutropenic murine thigh and lung infection models in which the infections were caused by a variety of Gram-negative bacilli. The dose fractionation study using the thigh infection model in which the infection was caused by Pseudomonas aeruginosa showed that the cumulative percentage of a 24-h period that the free drug concentration in plasma exceeds the MIC (%fT>MIC) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 27 publications
1
91
1
Order By: Relevance
“…The results of the in vitro chemostat model using iron-depleted cation-adjusted Mueller-Hinton broth (ID-CAMHB) were consistent with the observation from several in vivo animal studies, which have been used to evaluate the potential use of cefiderocol to treat the infections caused by carbapenem-resistant Gram-negative bacteria with a MIC of ≤4 μg/ml. The PK/PD studies using mouse thigh infection models caused by a variety of Gram-negative bacteria showed that a 1-log 10 reduction in bacteria burden at 24 h was associated with 75% of the percentage of time that free cefiderocol concentrations are above the MIC (% fT MIC ) on average ( 16 ). The Monte-Carlo simulation showed that a dose of 2 g every 8 h as a 3-h infusion provided >90% probability of target attainment with a pharmacodynamic target of 75 or 100% % fT MIC for a MIC of ≤4 μg/ml in nosocomial pneumonia patients ( 17 ).…”
Section: Textmentioning
confidence: 99%
“…The results of the in vitro chemostat model using iron-depleted cation-adjusted Mueller-Hinton broth (ID-CAMHB) were consistent with the observation from several in vivo animal studies, which have been used to evaluate the potential use of cefiderocol to treat the infections caused by carbapenem-resistant Gram-negative bacteria with a MIC of ≤4 μg/ml. The PK/PD studies using mouse thigh infection models caused by a variety of Gram-negative bacteria showed that a 1-log 10 reduction in bacteria burden at 24 h was associated with 75% of the percentage of time that free cefiderocol concentrations are above the MIC (% fT MIC ) on average ( 16 ). The Monte-Carlo simulation showed that a dose of 2 g every 8 h as a 3-h infusion provided >90% probability of target attainment with a pharmacodynamic target of 75 or 100% % fT MIC for a MIC of ≤4 μg/ml in nosocomial pneumonia patients ( 17 ).…”
Section: Textmentioning
confidence: 99%
“…Compared to cefepime, which showed %fT > MIC of 61.7% and 87.7% to reach a bacterial stasis and a 1 log10 CFU reduction, cefiderocol demonstrated lower values of %fT > MIC of 47.5% and 57.6%, respectively [26]. To achieve a 1-log10 reduction, %fT > MIC for Enterobacteriaceae and P. aeruginosa in the thigh infection models were 73.3% and 77.2%, respectively [26]. Against Enterobacteriaceae, P. aeruginosa, A. baumannii, and S. maltophilia in the lung infection model, %fT > MIC were 64.4%, 70.3%, 88.1%, and 53.9%, respectively [26].…”
Section: Animal Studiesmentioning
confidence: 75%
“…To achieve a 1-log10 reduction, %fT > MIC for Enterobacteriaceae and P. aeruginosa in the thigh infection models were 73.3% and 77.2%, respectively [26]. Against Enterobacteriaceae, P. aeruginosa, A. baumannii, and S. maltophilia in the lung infection model, %fT > MIC were 64.4%, 70.3%, 88.1%, and 53.9%, respectively [26]. A. baumannii required higher %fT > MIC values than those for Enterobacteriaceae and P. aeruginosa, which demonstrated similar efficacy in both thigh and lung infection models [26].…”
Section: Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations